Information availability for educational management in Nigerian universities: options for reforms (2012)
Information has been recognized as an essential ingredient in educational management. It has been observed that most studies focus on information generation with the assumption of its availability once generated, hence this study investigated the availability of information for educational management in Nigerian Universities. The study investigated Information Communication Technology (ICT) equipment availability among stakeholders (lecturers and students) in universities, copiously examining databases, websites/web portals, Local Area Networks (LAN) and Wide Area Networks (WAN) availability. A total of 7,160 respondents representing 11% of total population were drawn from first and second generation universities that cut across the six geo-political zones of Nigeria. Two researcher-designed instruments titled 'Information Availability and Management of Education in Nigerian Universities Questionnaire (IAMENUQ) I and II that yielded ‘r’ -0.602 and 'r-0.76' were used to elicit responses after due validation. While all independent variables recorded 100% availability, LAN recorded 72% deficiency and unavailability. It was further observed that a significant relationship existed between Information Availability (IA) and Educational Management (EM) at r-0.260 and r-0.443 when p<0.05 respectively in Nigerian universities. Information availability cannot be overlooked when implementing educational programmes in tertiary institutions. Policy makers are therefore implored to plan information resources adequately to enhance its good availability and utilization.